Foodways in prehistoric Cyprus: a view from the Kouris valley during the 5th and 4th millennia cal BC - Voskos, Ioannis; Kloukinas, Dimitris; Georgotas, Anastasios; Marda-Stypsianou, Antonia; Roumpou, Maria; Vika, Efrossini; Mantzourani, Eleni (Journal of Greek Archaeology, 2023)
Food-related activities are of particular significance when attempting to reconstruct past and present lifeways. As has been suggested, cooking practices transform nature into culture, whereas dining in both everyday and ritual contexts turns culture into social life. Food itself is a language and a powerful symbol embodying structural principles, belief systems and taboos related to cultural and individual identities. It is also inextricably linked to various aspects of social interaction, including the creation and negotiation of group membership, social boundaries and status. Food acquisition, production, distribution, consumption and discard practices are, therefore, closely entwined with the multi-faceted realities of everyday life, while their social significance remains negotiable and polysemic.